Cenários do uso das redes elétricas inteligentes (smart grid): tendências de sua difusão no Brasil - Schettino, Stevon (2013)
The Smart Grid is considered the most promising technology conglomerate to be applied to operational improvement and optimization of the entire supply chain of electricity, which is gaining popularity in electric utilities, research institutes and telecommunications companies. The objective of this work is to perform the projection scenarios to assess the trend of diffusion of Smart Grid in Brazil, presenting the main challenges the country may face, as well as explore and present the concepts of Smart Grid and its global evolution. For this, we conducted a documentary analysis of current legislation in the electricity sector, as well as a literature search in several international and national journals to understanding the concepts of Smart Grid, its benefits and impacts on the value chain of the electric system, the barriers to their diffusion in Brazil and the paths of investment incentives for deployment of new technology. To support the development of the scenarios we conducted a literature review on the main methods and techniques for developing scenarios and their main characters (authors), and set the Global Business Network - GBN, supported by Stakeholder Analysis (through knowledge from industry experts), the most appropriate methodology in this research environment for the design of scenarios and assessing trends diffusion of Smart Grid in Brazil. Comes to the conclusion, through the survey and the three scenarios prepared, that they point to a long and challenging journey in the development and deployment of Smart Grid technology in Brazil, which is still in an embryonic phase of project implementation pilot for development of technology and knowledge, having to overcome regulatory, financial, political, social, cultural and technological barriers. This trajectory can and should be simplified through government action, establishing sector policies favorable to the spread of the Smart Grid, with goals and deadlines, as well as the definition of a specific regulatory framework to regulate the electricity sector on this matter.